Dietary supplements - Maughan, R. J.; King, D. S.; Lea, T. (Journal of Sports Sciences, 2004)
For the athlete training hard, nutritional supplements are often seen as promoting adaptations to training, allowing more consistent and intensive training by promoting recovery between training sessions, reducing interruptions to training because of illness or injury, and enhancing competitive performance. Surveys show that the prevalence of supplement use is widespread among sportsmen and women, but the use of few of these products is supported by a sound research base and some may even be harmful to the athlete. Special sports foods, including energy bars and sports drinks, have a real role to play, and some protein supplements and meal replacements may also be useful in some circumstances. Where there is a demonstrated deficiency of an essential nutrient, an increased intake from food or from supplementation may help, but many athletes ignore the need for caution in supplement use and take supplements in doses that are not necessary or may even be harmful. Some supplements do offer the prospect of improved performance; these include creatine, caffeine, bicarbonate and, perhaps, a very few others. There is no evidence that prohormones such as androstenedione are effective in enhancing muscle mass or strength, and these prohormones may result in negative health consequences, as well as positive drug tests. Contamination of supplements that may cause an athlete to fail a doping test is widespread.